Development of a Rat Sandwich-Cultured Hepatocytes Model Expressing Functional Human Organic Anion Transporting Polypeptide (OATP) 1B3: A Potential Screening Tool for Liver-Targeting Compounds - Taleah Farasyn; Chao Xu; Wei Yue (Frontiers Media S.A., 2021)
Purpose: Organic anion transporting polypeptide (OATP) 1B3 transports many clinically important drugs, including statins, from blood into the liver. It exclusively expresses in human liver under normal physiological conditions. There is no rodent ortholog of human OATP1B3. Tissue targeting of therapeutic molecules mediated by transporters, including liver-targeting via liver-specific OATPs, is an emerging area in drug development. Sandwich-cultured primary hepatocytes (SCH) are a well characterized in vitro model for assessment of hepatic drug uptake and biliary excretion. The current study was designed to develop a novel rat SCH model expressing human OATP1B3 to study the hepatic disposition of OATP1B3 substrates. Methods: Primary rat hepatocytes transduced with adenoviral vectors expressing FLAG-tagged OATP1B3 (Ad-OATP1B3), a control vector Ad-LacZ, or that were non-transduced were cultured in a sandwich configuration. FLAG immunoblot and immunofluorescence-staining determined expression and localization of OATP1B3. Uptake of [3H]-cholecystokinin octapeptide (CCK-8), a specific OATP1B3 substrate, was determined. Taurocholate (TC) is a substrate routinely used in SCH to assess biliary excretion via bile canaliculi (BC) and is also a substrate of OATP1B3. [3H]-TC accumulation in cells+BC, cells, biliary excretion index (BEI) and in vitro Clbiliary were determined using B-CLEAR® technology. Results: OATP1B3 protein was extensively expressed and primarily localized on the plasma membrane in day 4 Ad-OATP1B3-transduced rat SCH. [3H]-CCK-8 accumulation in cells+BC was significantly greater (~5-13 folds, p<0.001) in day 4 SCH with vs. without Ad-OATP1B3-transduction. Expressing OATP1B3 in rat SCH significantly increased [3H]-TC accumulation in cells+BC and cells, without affecting BEI and in vitro Clbiliary. Conclusions: Rat SCH expressing human OATP1B3-is a novel in vitro model allowing simultaneous assessment of hepatic uptake, hepatocellular accumulation and biliary excretion process of a human OATP1B3 substrate. This model could be a potential tool for screening for liver-targeting compounds mediated by OATP1B3.